Noninvasive Detection of Matrix Metalloproteinase Activity In Vivo using a Novel Magnetic Resonance Imaging Contrast Agent with a Solubility Switch - Martin Lepage; William C. Dow; Marco Melchior; Ying You; Barbara Fingleton; C. Chad Quarles; Claude Pépin; John C. Gore; Lynn M. Matrisian; J. Oliver McIntyre (Molecular Imaging)
We have developed novel proteinase-modulated contrast agents (PCAs) to detect the activity of proteinases in vivo using magnetic resonance imaging. The PCAs are based on the concept of a solubility switch, from hydrophilic to hydrophobic, that significantly modifies the pharmacokinetic properties of the agent as revealed by the slow efflux kinetics from the activity site. Our compound PCA7-switch detects the activity of the secreted matrix-degrading proteinase matrix-metalloproteinase 7 (MMP-7) in living, tumor-bearing mice. Control experiments were performed using an agent that was not cleaved by MMP-7 (PCA7-scrambled), an agent that could be cleaved by MMP-7 but lacked the solubility switch (PCA7-B), and a standard contrast agent (gadolinium–diethylenetriaminepentaacetic acid). PCA7-switch detected a reduction in MMP-7 activity in tumor-bearing mice treated with a synthetic MMP inhibitor, demonstrating its effectiveness in noninvasive functional imaging of proteolytic activity in vivo.